Studying the effect ZnONP Deposited on ST37-2 by Pulse Laser Depositions Technique for Corrosion Protection Using in Oil Storage Applications. - Abbas, Ahmed S.; Annon, Iman Adnan; Sayyid , Firas F. (Journal of Petroleum Research and Studies, 2022)
In the study, zinc oxide nanoparticles (ZnONP) were coated on carbon steel substrates via pulse laser deposition (PLD) process, in order to achieve passive layers of nanocoating. ST37-2 a type of steel is used in the manufacture of tanks that are used in oil applications, which suffers from corrosion, this will lead a large losses. Electrochemical technique (Tafel polarization completion) has been carried out for study the corrosion behavior of this steel coating type. The specimens of steel were examined in aqueous solution containing about 3.5 wt. % NaCl using polarization method, with power of hydrogen (pH) held to value 4.0, in order to evaluated the corrosion rate. ZnONP. Characteristics and topographic nanocoating by PLD technique were evaluated by Field Emission Scanning Electron Microscope (FESEM) and X-ray Diffraction (XRD) tests. Where semi uniform nanoparticles of ZnONP were achieved with a nanoscale approximately ranging from 33-56 nm, While XRD pattern indicated the presence of ZnONP with different crystal structures. In other side the input parameters of (PLD) technique were substrate temperature, number of pulse and fluencies energy have been examined, in order to study their influence on the rate of corrosion reduction. The results indicate that number of shoots pulse has a significant effect the corrosion rate in operation of PLD technique, which is highest among the contributions of the other parameters. Enhancement about 56% is achieved of ST37-2 coated with (ZnONP) deposition, as compared with uncoated steel.